(untitled) (BIRDEM Medical Journal, 2012)
Mucormycosis is a form of fulminant invasive fungal infection of the sinonasal tract that often extends to the orbit, brain, palate, and skin. It is caused by members of the order Mucorales, and it is considered to be the most fatal fungal infection known to man. It is most commonly associated with diabetic ketoacidosis, hematologic malignancies, acquired immunodeficiency syndrome acquired immunodeficiency syndrome, see AIDS. , and immunosuppressive therapy. This rare opportunistic infection exists in many forms, the most common of which is rhinocerebral mucormycosis. Treatment includes aggressive surgical debridement of the necrotic tissue combined with systemic antifungal therapy. In this case report, we describe the successful management of rhinoorbitocerebral mucormycosis, a subtype of the rhinocerebral variety, complicated by osteomyelitis of cranium. We review the diagnostic work-up and discuss the literature with respect to the presentation, pathophysiology, management, and outcome of the disease. DOI: http://dx.doi.org/10.3329/birdem.v2i2.12331 (Birdem Med J 2012; 2(2):124-127)